قيود السياسة الخارجية العراقية بعد عام 2021 (قضايا سياسية, 2022)
It is important to study the constrains of the Iraqi foreign policy after 2021, by getting to know the objectives of the Iraqi foreign policy . The Iraqi external political decision- making process faces internal restrictions represented by the restriction of the internal political system and external restrictions represented by regional and international restrictions . but confronting terrorist threats is the biggest challenge facing Iraqi foreign policy . It is imperative for the Iraqi foreign policy to activate the performance of the external political decision-making unit to face regional and international developments . The future challenges facing Iraqi foreign policy can be overcome if the Iraqi foreign policy manages to employ regional and international variables to achieve the Iraq national interest.